THE PROTECTION TO CHILDREN OF DUAL CITIZENSHIP IN POSSESSING TITLE ON LAND IN INDONESIA - Arianto, Dian (Yustisia, 2017)
This juridical-normative research aims to identify and analyze the protection of the proprietary rights of children born under mixed marriages over ownership right and ownership right conveyance process for children with dual citizenship. The research results indicated that the legal protection on ownership right proprietary rights of children under mixed marriages can be enjoyed by the children by choosing Indonesian as their citizenship at most 1 year after obtaining such bequest over the land. When the children choose foreign citizenship, then they must pass the ownership rightover the land. The transfer process on the land requires the children to be at least 18 years of age or married and cannot be represented by foreign parents/custodians, and thus a trustee is appointed based on District Court’ ruling.